2020
DOI: 10.3389/fmolb.2020.00146
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 Is a Potential Therapeutic Target for Echovirus 9 Infection

Abstract: Echovirus is an important cause of viral pneumonia and encephalitis in infants, neonates, and young children worldwide. However, the exact mechanism of its pathogenesis is still not well understood. Here, we established an echovirus type 9 infection mice model, and performed two-dimensional gel electrophoresis (2DE) and tandem mass spectrometry (MS/MS)-based comparative proteomics analysis to investigate the differentially expressed host proteins in mice brain. A total of 21 differentially expressed proteins w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Some of the top upregulated genes are ISG15, IFIT3, IRF7, and BST2 which play roles in response to viruses. In NK cells there are many up and down regulated genes as seen in 6D, some of the top upregulated genes are NXF1 , which is involved in transport of unspliced retroviral genomic RNA and CAPZA1 which was downregulated, and is also observed to be downregulated in virus infected cells(24, 25).…”
Section: Resultsmentioning
confidence: 98%
“…Some of the top upregulated genes are ISG15, IFIT3, IRF7, and BST2 which play roles in response to viruses. In NK cells there are many up and down regulated genes as seen in 6D, some of the top upregulated genes are NXF1 , which is involved in transport of unspliced retroviral genomic RNA and CAPZA1 which was downregulated, and is also observed to be downregulated in virus infected cells(24, 25).…”
Section: Resultsmentioning
confidence: 98%
“…Tembusu virus [43], enterovirus 71 [44], and echovirus 9 [45], in which HSP70 functioned as receptor, supplemental receptor, or accessory factor that facilitates viral binding to host cells and viral entry. Based on the findings of this study, we suggest that HSP70 of B. mori could be employed by DpCPV to facilitate viral attachment and cell entry.…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 is a 70 kDa housekeeping protein chaperone located on the cell surface of several prokaryotes and eukaryotes cells, and it is responsible for assuring nascent protein folding, refolding misfolded proteins, and facilitating protein transportation [36]. Research indicated that HSP70 contributes to the attachment and cell entry of multiple viruses such as rotavirus [21], dengue virus [37], Japanese encephalitis virus [38], Marek’s disease virus [39], Hazara virus [40], Chikungunya virus [41], grass carp reovirus [42], Tembusu virus [43], enterovirus 71 [44], and echovirus 9 [45], in which HSP70 functioned as receptor, supplemental receptor, or accessory factor that facilitates viral binding to host cells and viral entry. Based on the findings of this study, we suggest that HSP70 of B. mori could be employed by DpCPV to facilitate viral attachment and cell entry.…”
Section: Discussionmentioning
confidence: 99%
“…However, depending on the virus type, its effects on host protein expression, and physiological metabolism, they can be severe and life-threatening (Wang et al 2020). Echovirus infections affect infants and neonates the most, with echoviruses accounting for the majority of Enterovirus infections in newborns under the age of two months , in Neonatal Intensive Care Unit (NICU) outbreaks, Echovirus infections are extremely dangerous, accounting for 15-30% of nosocomial viral infections and resulting in neonatal death in up to 25% of cases (Civardi et al 2013).…”
Section: Introductionmentioning
confidence: 99%